Determinants of Welfare Based on the Human Development Index in Central Sulawesi Province - Mangkona, Andi Subadir; Busnetty, Ida; Nurariyani, Dika (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the determinants of public welfare, measured by the Human Development Index (HDI), in Central Sulawesi Province. The data used are secondary data from the Central Bureau of Statistics (BPS) and the Ministry of Finance for the period 2017-2023. The study analyzes the impact of the open unemployment rate, population size, government capital expenditure, poverty rate, and inflation on the HDI using the Fixed Effect Model (FEM) panel data regression method. The relationship among these variables is conceptually supported by Human Capital Theory, Keynesian Consumption Theory, and Endogenous Growth Theory, which explain how unemployment, inflation, and investment affect development outcomes. The results show that the open unemployment rate, poverty rate, and inflation have a significant negative effect on the HDI. On the other hand, population size and government capital expenditure have a positive but insignificant effect on the HDI. These findings confirm existing research while also offering context-specific insights: the ineffectiveness of capital expenditure indicates suboptimal policy implementation in improving education, health, and infrastructure outcomes related to HDI.